Nitrous Oxide Dynamics in Agricultural Peat Soil in Response to Availability of Nitrate, Nitrite, and Iron Sulfides. Issue 1 (2nd January 2020) - Taghizadeh-Toosi, Arezoo; Clough, Tim; Petersen, Søren O.; Elsgaard, Lars
Abstract: Drained agricultural peat soils are potential hot spots of nitrous oxide (N2 O) emissions, but the biogeochemical basis for distinctively large emissions is still unclear. Incubation experiments with acidic bog peat, using nitrate (NO3 − ), nitrite (NO2 − ), synthetic iron monosulfide (FeS), and ground natural pyrite (FeS2 ), suggested that heterotrophic denitrification of nitrate and nitrite was a major potential source of N2 O in the peat soil. Neither FeS nor FeS2 amendment affected N2 O production and therefore high production potentials of N2 O were not a result of interactions between N oxyanions and iron sulfides, such as chemolithoautotrophic pyrite oxidation.